Why don't we do it in our sleeves? - Lounsbury, Ben.; OtoRhinoLounsburgology Productions (United States : OtoRhinoLounsburgology Productions, 2007)
Demonstrates recommended techniques for coughing and sneezing to reduce disease transmission.
DVD, region free; NTSC; full screen presentation.
Audio tracks in English, French and Spanish.
Closed captioned.
Includes French and Spanish language version with English subtitles; and director's commentary for infection control officers, teachers, videographers, and others with special interest in the subject.
Keywords: Hygiene -- Video recordings; Communicable diseases -- Transmission -- Videorecordings; Infection -- Prevention -- Videorecordings; Documentary films; Short films; Video recordings for hard of hearing people